Characterization of a chemostable serine alkaline protease from Periplaneta americana - Sanatan, Prashant T.; Lomate, Purushottam R.; Giri, Ashok P.; Hivrale, Vandana K. (BMC Biochemistry, 2013)
Background: Proteases are important enzymes involved in numerous essential physiological processes and hold a strong potential for industrial applications. The proteolytic activity of insects' gut is endowed by many isoforms with diverse properties and specificities. Thus, insect proteases can act as a tool in industrial processes. Results: In the present study, purification and properties of a serine alkaline protease from Periplaneta americana and its potential application as an additive in various bio-formulations are reported. The enzyme was purified near to homogeneity by using acetone precipitation and Sephadex G-100 gel filtration chromatography. Enzyme activity was increased up to 4.2 fold after gel filtration chromatography. The purified enzyme appeared as single protein-band with a molecular mass of similar to 27.8 kDa in SDS-PAGE. The optimum pH and temperature for the proteolytic activity for purified protein were found around pH 8.0 and 60 degrees C respectively. Complete inhibition of the purified enzyme by phenylmethylsulfonyl fluoride confirmed that the protease was of serine-type. The purified enzyme revealed high stability and compatibility towards detergents, oxidizing, reducing, and bleaching agents. In addition, enzyme also showed stability towards organic solvents and commercial detergents. Conclusion: Several important properties of a serine protease from P. Americana were revealed. Moreover, insects can serve as excellent and alternative source of industrially important proteases with unique properties, which can be utilized as additives in detergents, stain removers and other bio-formulations. Properties of the P. americana protease accounted in the present investigation can be exploited further in various industrial processes. As an industrial prospective, identification of enzymes with varying essential properties from different insect species might be good approach and bioresource.
Keywords: Chemostability; Industrial catalyst; Insect proteases; Periplaneta americana; Serine alkaline protease

Compensatory proteolytic responses to dietary proteinase inhibitors from Albizia lebbeck seeds in the helicoverpa armigera larvae - Hivrale, Vandana K.; Lomate, Purushottam R.; Basaiyye, Shriniwas S.; Kalve, Neeta D. (Arthropod-Plant Interactions, 2013)
Plant proteinase inhibitors (PIs) have been shown to reduce the growth rates in larvae of numerous insect species. On the other hand, insects can also regulate their proteinases against plant PIs. In the present study, we report the compensatory activities of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) gut proteinases against the PIs of Albizia lebbeck seeds. Total of ten proteinase inhibitor bands were detected in the seed extract of A. lebbeck. Bioassays were conducted by feeding H. armigera larvae on diet containing partially purified PIs from A. lebbeck seeds. Results show that larval growth and survival was significantly reduced by A. lebbeck PIs. We found that higher activity H. armigera gut proteinase (HGP) isoforms observed in the midgut of control larvae were inhibited in the midgut of larvae fed on test diet. Some HGP isoforms were induced in the larvae fed on PI containing test diet; however, these isoforms showed lower activity in the larvae fed on control diet. Aminopeptidase activities were significantly increased in the midgut of larvae fed on test diet. A population of susceptible and resistant enzymes was observed in the midgut of H. armigera, when fed on diet containing PIs from A. lebbeck seeds. Our initial observations indicate that H. armigera can regulate its digestive proteinase activity against non-host plant PIs, too. It is important to study the exact biochemical and molecular mechanisms underlying this phenomenon in order to develop PI-based insect control strategies.
Keywords: Albizia lebbeck; Helicoverpa armigera; Midgut proteinases; Proteinase inhibitors; regulation